Endoscopic submucosal dissection for gastric tumors in various types of remnant stomach - Ojima, Toshiyasu; Takifuji, Katsunari; Nakamura, Masaki; Nakamori, Mikihito; Katsuda, Masahiro; Iida, Takeshi; Hayata, Keiji; Iwahashi, Makoto; Yamaue, Hiroki (Endoscopy, 2014)
Background and study aims: The aim of this study was to examine the clinical outcomes of endoscopic submucosal dissection (ESD) for gastric tumors in various types of remnant stomach.Patients and methods: Between January 2002 and March 2013, ESD was performed for 750 gastric tumors. Of these lesions, 49 were in a remnant stomach, and were included in the study.Results: The en bloc resection rate was 100 %. The curative resection rate was 82 %. The rate of perforation was high in patients with gastric conduits (28.6 %). Perforation was significantly more common in patients with lesions located on the suture line (4.9 % vs. 50.0 %; P = 0.0043). Conclusion: ESD for gastric tumors in the remnant stomach can be considered feasible and safe in clinical practice. However, the procedure is technically more difficult in patients with a gastric conduit, due to the increased risk of perforation at the suture line.